Dominant dystrophic epidermolysis bullosa with congenital absence of skin and brachydactyly of the great toes. Issue 5 (2nd August 2021) - Sawka, Erika; Funk, Tracy
Abstract: Epidermolysis bullosa (EB) encompasses a phenotypically and genetically heterogeneous group of inherited skin disorders characterized by blistering and erosions of the skin with minimal trauma. Dystrophic EB (DEB), both dominant and recessive, can be associated with several extracutaneous manifestations, including musculoskeletal deformities. Congenital deformities of the feet have rarely been reported in the literature. We describe an infant with dominant DEB and congenital absence of the skin who presented with congenital brachydactyly of the bilateral great toes.